The framing of the African National Congress? 55th national conference by international online news media - Kalimashe, Nombulelo (Centre for Film and Media Studies, 2025)
African National Congress (ANC) hosts a national conference every five years. The national conference also referred to as the elective conference is a significant political event in South Africa because apart from electing new national leadership some of whom ultimately lead the country, it also outlines the political strategic direction as it relates to policy formulation, constitutional matters and the administration of government (Nantylya, 2018). As such over the years, the elective conferences of the ANC have garnered significant media attention both nationally and abroad (Booysen, 2019). These conferences have historically attracted media attention from around the world, particularly in the period leading up to, during and post the conference (Booysen, 2019). Accordingly, during these conferences, the media plays a crucial role in informing the public about the discussions, policy issues, election processes, candidates, and election results. It is meant to be a platform of enriched discourse. To this end, the media serves as a public forum or conduit for meaningful public participation on matters of political, economic, and social significance during political events, in particular those involving elections (Cushion and Jackson, 2019:986). In this capacity, the media should be a nonpartisan institution that serves the public interest, presenting all perspectives and allowing the public to make its own decisions. Entman (1993) and Cushion and Jackson (2019) have found that this is not always the case. Pointedly, Entman (1993) has found that there are numerous competing factors that influence what and how events are portrayed in news coverage and that news coverage is not always neutral but is framed and packaged to serve specific interests, convey a particular message and have a particular intended result or influence. It is against this background that the research aims to analyse the selected international online newspapers coverage of the ANC's 55th election conference which took place in December 2022. Specifically, it will analyse how the conference was framed, what aspects of the conference were highlighted, to what extent the coverage highlighted some facts and not others– thereby possibly influencing the reader's perception of the 55th ANC conference. This was done to answer the primary research question: how was the ANC's 55th election conference framed in international daily online media. The study used the framing theory as its theoretical foundation and a qualitative methodology. The methodological approach selected was the most suitable when combined with content analysis and critical discourse analysis. As it enabled the evaluation of texts, language and communication in the context of larger social processes. It included theory-based literature and newspaper articles from international online daily newspapers. The study's datasets were compiled from primary and secondary sources acquired through a combination of Google searches and the Press Reader an electronic data repository with the temporal demarcation being between 1 January 2022 the start of the new year and 20 December 2022 four days after the conference. The study found five overarching frames, namely, A weak factionalised declining ANC, Ramaphosa the redeemer: the one who influences the rand and markets, Phala-Phala as a political ploy, Winners and Losers: Game framing the leadership contestation, The scandal- tainted Former Minister of Health Zweli Mkhize. The frames were identified, analysed and reported using critical discourse analysis. The study found that the coverage of the conference was influenced by societal discourses linked to the factional battles of the ANC, Cyril Ramaphosa's Phala Phala farm theft, and related issues. As such, the conference itself was not the primary focus of international publications' coverage.